Guidelines for Caribbean faith based organisations in developing policies and action plans to deal with HIV/AIDS (Canadian International Development Agency CA, 2004)
Advocates the development and activation of policies and action plans for dealing with HIV/AIDS by religious institutions in the Caribbean.
Keywords: HIV